Toxic epidermal necrolysis and hemophagocytic lymphohistiocytosis: a case report and literature review - Sniderman, Jonathan D S (Clin Case Rep, 2015)
Diagnostic criteria for hemophagocytic lymphohistiocytosis should be reviewed early in critically ill patients with toxic epidermal necrolysis, multisystem dysfunction, and a deteriorating clinical trajectory.